1983
DOI: 10.1111/j.2044-8295.1983.tb01867.x
|View full text |Cite
|
Sign up to set email alerts
|

Spelling errors in context

Abstract: This paper looks at the spelling errors that occurred in the spontaneous writing of 12-year-old children. A number of errors occur that are not addressed by the conventional approaches to spelling and which we can best understand by taking account of the psychological context in which they occur. One set of errors relates more to incorrect articulation than to poor spelling. A second set indicates the role of morphemic factors in the spelling of inflected words. Two other sets, one consisting of lexical substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 1 publication
4
29
0
1
Order By: Relevance
“…When we view these errors at the morphological level, we may interpret that the root morpheme and the inflection morpheme are being compartmentalized, thus displaying the difficulty in making accurate combinations of these two morphemes. This corresponds with Sterling (1983), who found similar errors underscoring that the errors of this nature are 'morpho-orthographic, the graphemic forms of root morpheme and inflection morpheme stored separately in the internal lexicon [and] retrieved when an item is to be spelt and put together after the application of the appropriate adjustment' (p. 356). However, at the syntactic level, these deviations may further contribute to making associations with the grammar of subject-verb agreement deviation.…”
Section: Errors Of Omissionsupporting
confidence: 73%
See 1 more Smart Citation
“…When we view these errors at the morphological level, we may interpret that the root morpheme and the inflection morpheme are being compartmentalized, thus displaying the difficulty in making accurate combinations of these two morphemes. This corresponds with Sterling (1983), who found similar errors underscoring that the errors of this nature are 'morpho-orthographic, the graphemic forms of root morpheme and inflection morpheme stored separately in the internal lexicon [and] retrieved when an item is to be spelt and put together after the application of the appropriate adjustment' (p. 356). However, at the syntactic level, these deviations may further contribute to making associations with the grammar of subject-verb agreement deviation.…”
Section: Errors Of Omissionsupporting
confidence: 73%
“…Sterling (1983) underscores such errors as 'not incorrect spellings of the correct sounds but rather correct spelling of incorrect sounds' (p. 359). Additionally, the study also revealed an interesting error in writing 'studiem' for 'stadium' and 'housepetal' for 'hospital'.…”
Section: Errors Of Substitutionmentioning
confidence: 99%
“…Moreover, many words that contain more than one morpheme are more opaque than are words such as waiting. A child may not know that magician is related to magic, for example, and so may not spell the two words in a similar manner (e.g., Sterling, 1983). Children's knowledge about the morphological relationships among the words in their spoken vocabularies increases as they develop (e.g., Carlisle & Fleming, 2003), and with it their ability to use these relationships for the benefit of spelling.…”
mentioning
confidence: 99%
“…Em relação à segunda hipótese, evidências empíricas vêm de estudos transversais (Carlisle, 1988;Sterling, 1983) e longitudinais (Nunes et al, 1997a(Nunes et al, , 1997b. A ênfase da investigação está no padrão de desenvolvimento de estratégias usadas na escrita, como das habilidades que possam explicar o seu emprego.…”
unclassified